Pengaruh Faktor-Faktor Fundamental terhadap Return Saham LQ-45 di Bursa Efek Indonesia - Nova Begawati (SAFE-Network, 2022)
This study aims to prove the influence of fundamental factors on LQ-45 stock returns on the Indonesia Stock Exchange. In this study two categories of fundamental factors are used, namely internal and external companies. External or macroeconomic factors are measured by inflation, exchange rates and interest rates. Internal or financial factors are used price earnings ratio, return on assets and return on equity. In this study 17 companies were consistently used in the LQ-45 group. The observation period used from 2013 - 2017. The type of data is secondary in the form of supporting instruments from the company's financial statements. To do the stages of hypothesis testing is done by using multiple regression models and t-statistical testing. Based on the results of testing the hypothesis it was found that inflation had a significant negative effect on stock returns received by investors investing in LQ-45 companies on the Indonesia Stock Exchange. Exchange rates and interest rates individually have a significant effect on stock returns, while price earnings ratio, return on equity and return on assets have no significant effect on stock returns received by investors in investing in LQ-45 companies listed on the Indonesia Stock Exchange.